PMU-Based Transmission Line Parameter Identification at China Southern Power Grid - Zhou Huafeng; Zhao Xuanyu; Shi Di; Zhao Huashi; Jing Chaoyang (Institute of Advanced Engineering and Science, 2014)
China Southern Power Grid Company (CSG) recently developed and implemented an online PMU-based transmission line (TL) parameter identification system (TPIS). Traditionally, TL parameters are calculated based on transmission tower geometries, conductor dimension, estimates of line length, conductor sags, etc. These parameters only approximate the effect of conductor sag and ignore the dependence of impedance parameters on temperature variation. Recent development in PMU technology has made it possible to calculate TL parameters accurately. The challenges are that such application requires highly accurate PMU data while the accuracy of PMU measurements under different working/system conditions can be uncertain. With a large number of PMUs widely installed in its system, CSG plans to improve and update the EMS database using the newly developed TPIS. TPIS provides an innovative yet practical problem formulation and solution for TL parameter identification. In addition, it proposes a new metric that can be used to determine the credibility of the calculated parameters, which is missing in the literature. This paper discusses the methodologies, challenges, as well as implementation issues noticed during the development of TPIS.